Highly reversible Na ion storage in N-doped polyhedral carbon-coated transition-metal chalcogenides by optimizing the nanostructure and surface engineering. Issue 39 (25th September 2018) - Pan, Yuelei; Cheng, Xudong; Gong, Lunlun; Shi, Long; Deng, Yurui; Zhang, Heping
Abstract : Polyhedral carbon-coated structural N-CoS2 @C nanoparticles are synthesized by a facile one-pot solvothermal technique and exhibit excellent sodium ion storage performance. Abstract : Transition-metal chalcogenides (TMCs) have been attracting widespread attention due to their high lithium/sodium storage capacity, wide availability, and enhanced safety. However, their practical applications are still suffering from high volume changes, poor electronic conductivity and low utilization of active materials, resulting in unsatisfactory electrochemical performance. In this study, a facile one-pot solvothermal method was developed to self-assemble and produce N-CoS2 @C composites. It was found from the experiments that the developed 3D polyhedral carbon-coated structure of N-CoS2 @C can effectively reduce the diffusion lengths of sodium ions and electrons. Carbon layer was also found firmly encapsulated the CoS2, where it can greatly release mechanical stresses under high volume change and also improve the electronic conductivity of active materials. The developed 3D polyhedral carbon-coated structure results in outstanding rate performance (738 mA h g −1 at 1 A g −1 reaching up to 86.2% theoretical capacity and 450 mA h g −1 even at 10 A g −1 ) and extraordinary cycle stability (559 mA h g −1 at 1 A g −1 after 1000 cycles) when used as anode materials for sodium-ion batteries (SIBs). The research outcomes provide a novel design strategy for high-performance TMC electrodes and also a facile approach to fabricate promising anode materials for high-performance SIBs.